Current status and trends of illegal trade in hawksbill turtle products in Hainan Island, China - Ji, Xinyu; Wang, Zhao; Zhang, Ting; Chen, Dehui; Yang, Wenxiang; Li, Meimei; Shi, Haitao; Lin, Liu (Frontiers in Marine Science, 2024)
Introduction Illegal wildlife trade is among the most profitable illegal businesses worldwide. The hawksbill turtle (Eretmochelys imbricata), which has been listed as Critically Endangered on the IUCN Red List, has long been a prominent target of illegal wildlife trading worldwide, thus posing a substantial threat to its continued survival. In China, although Hainan Island is the largest trading area and the most important transit point for the illegal trade of hawksbill turtles, very few investigations of this trade have been conducted here. Methods In this study, from 2019 to 2020, we conducted field investigations to assess the extent of the illegal trade in hawksbill turtle products in nine cities on Hainan Island. Results Among the 878 shops surveyed in 2019, 157 shops (17.9%) sold hawksbill turtle products, totaling 6,208 pieces. In 2020, 122 shops (13.6%) of 895 surveyed shops sold such products, totaling 1,821 pieces. Thus, these findings indicate that the number of shops selling hawksbill turtle products and the total number of products sold declined in 2020. Among the surveyed cities, the highest levels of illegal trade in hawksbill turtle products were recorded in Haikou and Sanya, the capital city of Hainan and a renowned tourist city, respectively. Jewelry and craft shops were found to produce the most products, accounting for 98.0% of the shops surveyed. Accessories such as bracelets and necklaces accounted for the highest proportions of hawksbill turtle products, representing 72.5% and 92.9% of the total in 2019 and 2020, respectively. Discussion The observed decline in illegal trade in 2020 can be attributed to a combination of factors, including a strengthening of government law enforcement and supervision after the COVID-19 pandemic, a shift in illegal trade from offline to online activities, and a reduction in tourists. Law enforcement agencies should continue strict enforcement and supervision to effectively combat illegal trade, particularly in the key trading areas of Haikou and Sanya. Additionally, authorities should emphasize public education to increase awareness of wildlife conservation and relevant legislation. The findings of this study will serve as a vital reference for relevant law enforcement agencies, contributing to the effective combatting and prevention of the illegal hawksbill turtle trade in China.